Clinical and imaging outcomes after intermediate‐ or high‐risk pulmonary embolus. (1st September 2020) - Lachant, Daniel; Bach, Christina; Wilson, Bennett; Chengazi, Vaseem; Goldman, Bruce; Lachant, Neil; Pietropaoli, Anthony; Cameron, Scott; James White, R.
Abstract : Long‐term outcomes after acute pulmonary embolism vary from complete resolution to chronic thromboembolic pulmonary hypertension (CTEPH). Guidelines after acute pulmonary embolism are generally limited to anticoagulation duration. We assessed patients with estimated prognosis >1 year in our pulmonary hypertension clinic 2–4 months after treatment for intermediate‐ or high‐risk acute pulmonary embolism. At follow‐up, ventilation–perfusion scan and echocardiogram were offered. The aim of this study was to assess for recurrent symptomatic disease, residual imaging defects or right ventricular dysfunction, and functional disability after acute management of pulmonary embolism. After treatment for acute intermediate‐ or high‐risk pulmonary embolism, 104 patients followed up in pulmonary hypertension clinic. Of those, 55% of patients had self‐reported limitation in activity. No patients had symptomatic recurrence of pulmonary embolism. Forty‐eight percent of patients had residual perfusion defects on perfusion imaging, while 91% of patients had either normal or only mildly enlarged right ventricles. We identified heart failure preserved ejection fraction, iron deficiency, and obstructive sleep apnea as significant contributors to breathlessness. Treatment of these conditions was associated with improvement. Surprisingly, we diagnosed CTEPH in nine patients; for some, chronic thrombus may already have been present at the time of index evaluation. Our findings suggest that follow‐up in a dedicated pulmonary hypertension clinic 2–4 months after acute intermediate‐ or high‐risk pulmonary embolism may add value to patient care. We identified treatable comorbidities that could be contributing to post‐pulmonary embolism syndrome as well as CTEPH.